Effect of Supplemental Oxygen on Risk of Surgical Wound Infection - Din Muhammad Jamali, Ibad Ur Rahman, Hafiz Muhammad Ijazulhaq, Javeria Manzoor, Khurram Liaqat, Farah Naz, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: There is a risk of different complication after the surgery but delaying in wound healing or infection is one of most common risk. Oxidative killing is a process of tissues partial pressure of oxygen throughout the observed values ranges. The main defense against foreign particles in result of surgery is oxidative killing through neutrophils. In a study by Greif et al4 indicated oxygen 80% during the surgery and after 2 hours later of surgery 50% risk get lesser as compared to the patient who had administrated with 30% oxygen.4 Another study proved that chances of risk for infection get increase in patients who were administrated oxygen 11 % as compared to the patients with 25% oxygen administration.5 The current study was conducted to test the hypothesis that supplemental oxygen decreases the risk of post-operative wound infection. Objective: The objective of the study was to determine the effects of supplemental oxygen on risk of surgical wound infection. Materials and Methodology: A randomized Clinical Trial- double- blinded was conducted at DHQ hospital, Karachi from March 1, 2011 to October, 31, 2016. A total of 300 subjects with age around 18 to 80 years who underwent elective colorectal surgery and satisfying the inclusion and exclusion criteria were recruited in the study. Non-probability Purposive sampling technique was used to collect the data. Double-blinded technique was used. Blinded investigators diagnosed the wounds infection by following the criteria of centers of disease control and prevention. Patients were randomly allocated in two groups by sealed-envelope method. Baseline assessment was performed on each patient which included patient’s medical history, physical examination and Lab tests i.e. complete blood picture and biochemical analysis. Characteristics for patient’s baseline and aesthetic treatment were confound factors. 3rd generation antibiotics cephalosporin were administrated 1 to 2 hours before of surgery. Patients of Group 1 received oxygen fraction of inspired oxygen FIO2 of 30 and group 2 of 80 percent. Randomly chosen concentration flow of oxygen 16l/min was given. Patient was breathing ambient air. Supplemental oxygen was given to maintain the patient’s oxygen saturation to 92% that is measured by pulse oximetry. Patient’s treatment was slandered with antibiotics and anesthesia administration. For wound evaluation, tools used were National nosocomial infection surveillance scale 6 and Efficacy of infection control,7 Wounds were checked for infection on daily basis by surgeons who were blinded. And wound thought to be infected when they full fill the criteria of Centers for Disease control and prevention standard. Main outcome measure was surgical site for infection and secondary outcomes were recovery of bowl function, duration of hospital stay, ambulation and ability to absorb the solid food. Statistical Analysis: Analysis was done on SPSS by applying parametric and non-parametric test according to normality. Results: Results showed no significant difference in %age Surgical infection site, Daily ASEPSIS value ≥20 at any time (p-value<0.06), Admission in ICU (p-value= 0.74), Bowel function recovery (p-value=0.74), Solid food intake (p-value=0.54), Walking (p-value=0.57), Removal of Staples( 0.72), Duration of post-surgery hospitalization(p-value=0.09) of both the groups as p-value >0.05 of all variables. Practical implication: If we provide pre-operative supplemental oxygen it will be helpful to decrease SSI. Conclusion: Patients who received supplemental oxygen showed significantly decrease in the risk of wound infection. Hence, Pre-operative supplemental oxygen proved to be an effective intervention to decrease SSI in the patients having rectal or colon surgery. Keywords: ASEPSIS, Surgical Wound, Infection, Supplemental Oxygen